2015
DOI: 10.12669/pjms.316.8607
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pediatric procedural sedation & analgesiain a tertiary care hospital in Pakistan

Abstract: Background and Objective:Procedural sedation and analgesia (PSA) is pharmacologically induced state which allows patients to tolerate painful procedures while maintaining protective reflexes. It is the standard of care but there is limited data from Pakistan. Our objective was to assess the safety of the procedural sedation and analgesia in pediatric population at a tertiary care setting.Methods:A retrospective notes and record review was conducted at the Aga Khan University Hospital, Karachi over 4 years from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
3
4
0
Order By: Relevance
“…The evaluation of 1216 procedures included in our study showed safety and efficacy comparable to another study conducted by Haque et al, but the range of procedures assessed in our study is much larger [8]. In this study, we observed that a propofol dose of 1 mg/kg was enough for most patients in contrast to other studies in which higher doses were used [8][9]. There are other safe combinations like Mahajan et al suggested other combinations such as fentanyl and midazolam which are considered a safe regimen in children [16].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The evaluation of 1216 procedures included in our study showed safety and efficacy comparable to another study conducted by Haque et al, but the range of procedures assessed in our study is much larger [8]. In this study, we observed that a propofol dose of 1 mg/kg was enough for most patients in contrast to other studies in which higher doses were used [8][9]. There are other safe combinations like Mahajan et al suggested other combinations such as fentanyl and midazolam which are considered a safe regimen in children [16].…”
Section: Discussionsupporting
confidence: 79%
“…Relief from anxiety and procedural pain is ethically imperative in treating children from the fact that they tend to have short-and long-term physiological, physical as well as a psychological effect because of untreated pain [8]. Therefore, procedural sedation, described as the administration of medication for minimizing pain and awareness of the patients, is termed as the standard practice in the pediatric department's world over for facilitating procedures [9]. Although sedation is usually safe, it is sometimes associated with serious adverse events (SAEs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, Group H-S required more ketamine and propofol than Group L-S. Likewise our study, other studies administered both ketamine and propofol with or without premedication to children in procedural sedations [4,12,13]. In a study with 125 children, who had a procedure in the emergency department, only ketamine was administered as a sedative agent and required more doses (1.5-2 mg/kg) than in our study, in which we used multimodal sedatives ( 14).…”
Section: Discussionsupporting
confidence: 77%
“…However, pain assessment was recorded pre and post-procedure (during recovery). 8 The patient was discharged only when able to maintain good airway, was fully awake, presence of swallowing reflex, with ability to swallow clear liquids, and achieving the pre-sedation level of responsiveness.…”
Section: Methodsmentioning
confidence: 99%